Protocol for collaboration between the National Genebank and Community Seed Banks - Community Technology Development Trust; Seed Savers Network; National Agricultural Research Organisation, Uganda; Wageningen University & Research Centre; Alliance of Bioversity International and CIAT (Wageningen University & Research, 2020)
In recent years, national genebanks of some countries (e.g. Bhutan, Mexico, Nepal, South Africa and Uganda) have started to collaborate with community seed banks on the important task of conservation of crop (and tree) varieties. This collaboration has taken place in informal ways, in the form of participation in meetings and gatherings, seed and food fairs and through a number of joint activities, including the establishment of community seed banks and related (capacity development) activities. As far as is known, no formal agreements have been made/signed to structure, monitor and evaluate the collaboration in a more rigorous manner. Based on interactions among professionals from various countries who support community seed banks, it was decided to develop a generic collaboration protocol that could help shape the collaboration process in countries where this has not yet taken place or to solidify the process in countries where this is already happening. The protocol document includes chapters (articles) on the roles of the national genebank; the roles of community seed banks; principles of collaboration; activities that can be done together and rules and regulations for the collaboration. It benefitted from the inputs of many partners in Kenya, South Africa, Uganda and Zimbabwe and from the long community seed bank working experience of staff of Bioversity International, now the Alliance of Bioversity International and CIAT.